Do Startups Provide Employment Opportunities for Disadvantaged Workers? - Daniel Fackler; Michaela Fuchs; Lisa Hölscher; Claus Schnabel (Institute of Labor Economics (IZA), 2018)
This paper analyzes whether startups offer job opportunities to workers potentially facing labor market problems. It compares the hiring patterns of startups and incumbents in the period 2003 to 2014 using administrative linked employer-employee data for Germany that allow to take the complete employment biographies of newly hired workers into account. The results indicate that young plants are more likely than incumbents to hire older and foreign applicants as well as workers who have instable employment biographies, come from unemployment or outside the labor force, or were affected by a plant closure. However, an analysis of entry wages reveals that disadvantageous worker characteristics come along with higher wage penalties in startups than in incumbents. Therefore, even if startups provide employment opportunities for certain groups of disadvantaged workers, the quality of these jobs in terms of initial remuneration seems to be low.
Keywords: J31; J63; L26; M51; 330; startups; young firms; employment; wages; linked employer-employee data